Morellia Robineau-Desvoidy 1830 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Morellia Robineau-Desvoidy, 1830 Morellia Robineau-Desvoidy, 1830: 405. Type-species: Morellia agilis Robineau-Desvoidy, 1830 (= Musca hortorum Fallén, 1817), by designation of Townsend (1916: 8). Morellia aenescens Robineau-Desvoidy, 1830 Morellia aenescens Robineau-Desvoidy, 1830: 406. Type-locality: France, Saint-Sauveur. Syntypes, formerly in Robineau-Desvoidy collection, now destroyed (not MNHN). Siberian records: Sverdlovskaya Oblast’: Serov, Krasnoufimsk, Talizy, Verkhovino (Zagrebin, 1987a: 232); south part of Tyumenskaya Oblast’, subtaiga (Veselkin, 1966: 787); Kurganskaya and Novosibirskaya Oblast’ (Sorokina, 2006a: 226); Tomsk (Wnukovsky, 1936: 123); near Biysk (Sychevskaya, 1978: 82); Respublika Altay (Sorokina, 2006b: 139); valley of River Yenisey, northern taiga: Turukhansk, Verkhneimbatskoe, Yarzevo, Vorogovo, Kureyka, Igarka (Sychevskaya, 1974: 129); Altay, Pribaykal’e and Respublika Sakha [Yakutiya] (Zimin, 1951: 211); Siberia (Zimin & El’berg, 1970: 592); West and East Siberia (Pont, 1986a: 94). General distribution: Throughout the Palaearctic Region, from Europe to Japan. Morellia asetosa Baranov, 1925 Morellia asetosa Baranov, 1925: 59. Type-locality: Serbia: Topčider, near Belgrade. Lectotype ♂, CNC (designated by Pont, 1980: 313). Morellia simplicissima Zimin, 1951: 221. Type-localities: Russia, many localities in West Siberia, East Siberia, Russian Far East and Kazakhstan. Syntypes 25♂ ♀, ZIN (Pont, 2004: 92–93), and 1♀, MZPW (seen). Siberian records: Kurganskaya, Omskaya and Novosibirskaya Oblast’ (Sorokina, 2006a: 227); Smolino near Chelyabinsk, Krasnoyarskiy Kray: Minusinsk, Novoselovo, Manskiy Rayon (Sorokino), Irkutskaya Oblast’: Listvyanka [as “Irkutskiy Okrug, Listvenichnoe” in the original], Respublika Sakha [Yakutiya]: Yakutsk, Namshoe, Khamurgan near upper River Aldan (Zimin, 1951: 221, syntype localities of simplicissima ); Kurganskaya Oblast’ (Veselkin, 1989: 11); Respublika Tyva (Tamarina & Khromova, 1980: 81); South Tyva, River Naryn-gol (Pridantseva, 1967: ...